Answer:
The equation is y = 2x² + 7x + 5
Explanation:
In the quadratic equation y = ax² + bx + c
- The roots of it are the values of x at y = 0
- The sum of the two roots =
![(-b)/(a)](https://img.qammunity.org/2021/formulas/mathematics/college/haculr7rv8b7d3khvpnvw3pihr08hzmhcm.png)
- The product of the two roots =
![(c)/(a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xaly6nmhsorqt89ljradww8e52cvt4tpvz.png)
∵ The sum of the roots is
![(-7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/oms1s0g3t9b97gtk944cn4qduz7t5r5okk.png)
∵ The product of the roots is
→ By using the rules above
∴
=
![(-7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/oms1s0g3t9b97gtk944cn4qduz7t5r5okk.png)
∴
=
![(5)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2rxy6kw5kg24daxdgyet9la9ccq65iw0qn.png)
→ Compare between them
∴ a = 2
∴ -b = -7 ⇒ divide both sides by -1
∴ b = 7
∴ c = 5
∵ The form of the quadratic function is y = ax² + bx + c
→ Substitute the values of a, b, and c in it
∴ y = 2x² + 7x + 5
∴ The equation is y = 2x² + 7x + 5